RELIGIOUS AND PHILOSOPHICAL FOUNDATIONS OF HUMAN MORAL DEVELOPMENT (Conferencea, 2022)
In the article, an important factor of ensuring moral maturity, moral issues in world religions, religious-philosophical development made in our country during the historical development, as well as human moral maturity, the origins and sources of Islamic religion in the formation of moral development in a person are analyzed. Also, the role of religious education in the spiritual growth of young people in educating them as a conscientious, honest, and pure believer, and the important task of teaching moral education to the young generation using religious and philosophical sources were discussed.